Absence of superconductivity in fluorine-doped neptunium pnictide NpFeAsO. (27th July 2015) - Walters, A C; Walker, H C; Springell, R; Krisch, M; Bosak, A; Hill, A H; Zvorişte-Walters, C E; Colineau, E; Griveau, J-C; Bouëxière, D; Eloirdi, R; Caciuffo, R; et al.
Abstract: X-ray diffraction, specific heat, magnetic susceptibility and inelastic x-ray scattering measurements on the transurarium oxypnictides NpFeAsO and NpFeAsO0.85 F0.15 are presented. No superconductivity down to 2 K was observed upon fluorine doping, contrary to the structurally analogous rare-earth pnictides. No modification of the phonon density of states was observed upon doping with fluorine. We discuss our results in light of the latest experimental and theoretical studies on the role of phonons in the superconducting pnictide compounds.